PEDAGOGICAL SKILLS OF A MUSIC TEACHER - G.Shodiyeva (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article discusses pedagogical skill, the components of pedagogical skill, aspects that a teacher of modern education should take into account, and how the teacher’s skill is manifested in a musical culture lesson.